2014
DOI: 10.1021/nl404712t
|View full text |Cite
|
Sign up to set email alerts
|

Optical Field-Enhancement and Subwavelength Field-Confinement Using Excitonic Nanostructures

Abstract: We show that dye-doped polymers open an interesting route to controlling light at the nanoscale. Just as for the much better known metal-based plasmonic systems, propagating and localized modes are possible. We show that the attractive features offered by plasmonics, specifically enhanced optical fields and sub-wavelength field confinement, are also available with these materials. They thus open a new opportunity in nanophotonics in which fabrication and functionality might be achieved by harnessing molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(122 citation statements)
references
References 46 publications
(85 reference statements)
3
103
1
Order By: Relevance
“…Finally, we note that the SLRs might also arise as a result of exciton rather than plasmonic resonances [24].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Finally, we note that the SLRs might also arise as a result of exciton rather than plasmonic resonances [24].…”
Section: Discussionmentioning
confidence: 90%
“…The optical response of a metallic nanoparticle may be usefully considered from the perspective of the particle's polarizability, in particular the extinction cross section is easily derived from the polarizability [23,24]. The typical size of the particles in the work reported here was too large (size/λ ∼ 0.1) to allow the simplest approximation for the polarizability, i.e., the quasistatic polarizability, to be used.…”
Section: Introductionmentioning
confidence: 99%
“…Similar effects are expected for compounds including p-block elements in the near-infrared. 55,56 Interband plasmonic properties in the visible have been evidenced early 57 and re-visited in organic materials, [58][59][60] and have been demonstrated very recently for topological insulators. 61…”
Section: Interband Plasmonics: a New Paradigm In Photonics?mentioning
confidence: 99%
“…30 Recently, it has been theoretically shown that a nanosphere of TDBC-doped PVA displays enhanced optical fields and subwavelength field confinement analogously to plasmonic nanoparticles. 31 At present, however, spherical nanoparticles of J-aggregates have not been realized and the synthesis of high-quality nanospheres does not seem readily achievable.…”
mentioning
confidence: 99%